A DFT study of perovskite type halides KBeBr3, RbBeBr3, and CsBeBr3 in triclinic phase for advanced optoelectronic devices. (1st March 2022) - Hayat, Shafqat; Khalil, R.M. Arif; Hussain, Muhammad Iqbal; Rana, Anwar Manzoor; Hussain, Fayyaz
Abstract: The structural, electronic, magnetic, optical, vibrational, thermodynamic and mechanical properties of beryllium based perovskite type halides KBeBr3, RbBeBr3, and CsBeBr3 in triclinic phase have been investigated by utilizing PBE + GGA functional based on density functional theory in CASTEP simulation code. The determined lattice constants for considered perovskite type halides are listed as 5.7125 Å, 5.7202 Å and 5.9533 Å for KBeBr3, RbBeBr3, and CsBeBr3, respectively. The electronic properties have been determined and it is observed that these materials show insulator type character. The observed energy band gaps are in the order of 4.0 eV, 4.2 eV, and 4.7 eV for KBeBr3, RbBeBr3, and CsBeBr3, respectively as calculated by hybrid HSE06 functional. The optical properties like dielectric function, absorption coefficient, conductivity, extinction coefficient etc. also predict that the studied perovskite type halides are the potential candidate for optoelectronic devices. Additionally, the dynamic vibrational stability has been calculated and the determined phonon energy dispersion curves predict that these compounds are dynamically stable. Also, the thermodynamic parameters including enthalpy, free energy and temperature time's entropy have been investigated. Moreover, the mechanical and elastic properties of considered materials are also calculated to check their reliability, stability and easy handling for optoelectronic applications. This first principle investigation of computational properties of the novel materials implement an advance route to the theorists and experimentalists for the new potential applications in the renewable and advanced optoelectronic devices. Highlights: Studied compounds are wide band gaps semiconductors. The optical analysis predict the maximum absorption, minimum reflectivity and optical loss. Antiferromagnetic behavior with zero magnetic diploe moment is observed in all cases. The phonon energy dispersion curves revealed the dynamic stability with zero soft modes.